1997
DOI: 10.1177/0730888497024003006
|View full text |Cite
|
Sign up to set email alerts
|

The Institutionalization of the Sociology of Work in Latin America

Abstract: This overview of the recent intellectual history of the sociology of work in Latin America contextualizes this history in economic globalization and restructuring and political institutions in Latin America. The three-stage intellectual history addresses the development of a Latin American discipline whose theoretical models and empirical research strategies reflect crossnational similarities and variations in work, workers, and workplaces within Latin America and questions the acritical application of Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Labor studies in Latin America have generally tracked the impact of changes in the region’s politics, economic systems, and labor markets over the past decades (Abramo, 1998; Abramo et al, 1997; Cavalcanti, 2002; Cook, 1999, 2012; de la Garza Toledo & Pries, 1997). In the 1950s and 1960s research focused on the industrialization process linked to import-substitution-industrialization (ISI) policies.…”
mentioning
confidence: 99%
“…Labor studies in Latin America have generally tracked the impact of changes in the region’s politics, economic systems, and labor markets over the past decades (Abramo, 1998; Abramo et al, 1997; Cavalcanti, 2002; Cook, 1999, 2012; de la Garza Toledo & Pries, 1997). In the 1950s and 1960s research focused on the industrialization process linked to import-substitution-industrialization (ISI) policies.…”
mentioning
confidence: 99%
“…To some extent, this reality is a legacy of the debt crisis of the early 1980s, which pounded an emerging manufacturing sector and reduced prospects for growth that until then had looked promising (Amsden, 2001) and of the bleak “lost decade” of shrinking economies and rising unemployment that followed. The rich sociological exploration of the structural factors that shape employment in Latin America can arguably also be traced back to this historical moment of crisis and the economic changes it engendered (Abramo et al, 1997). At that moment, the examination of the world of work and the condition of workers in Latin America took on a renewed urgency and labor processes were considered with a keen eye to context, defined, at the time, by fragile and indeed imperiled democratic institutions, weak and co-opted labor unions, and the widespread prevalence of poverty and social exclusion.…”
mentioning
confidence: 99%
“…Through examinations of industries as varied but as specific as banking, textile production, petrochemicals, and telephone services, among others, researchers explored organizational changes in response to increasing globalization, the introduction of new technology, and shifts in the profile and subjectivity of the labor force. They have shown that the outcomes were extremely heterogeneous, generated by processes that were complex and informed by local and national contexts, by political junctures, and, most significantly, by the initiative of social actors, with workers chief among them (Abramo et al, 1997). The second area of exploration on which de la Garza Toledo’s anthology builds is the concern with atypical work.…”
mentioning
confidence: 99%
“… 4. Abramo and colleagues (1997), Abramo (1998), and Cavalcanti (2002) provide excellent reviews of recent studies in the sociology of work in Latin America. They show that, like our study, Latin American social scientists focus on issues of institutional change, state policies, neoliberalism, globalization, and worker power. …”
mentioning
confidence: 99%